Use Of E-Ddc to Improve Library Administrative Understanding in MI Jampang – Pangadaran (AbdimasMu UMTAS, 2025)
A collection of books with different genres, students can explore various kinds of knowledge. A well-managed book collection can make it easier for students and even school residents to read. The problem found in this school was the lack of teachers who understood the management of library administration so that the arrangement of book collections does not run properly. The role of teachers and librarians who understand in library management is very important so that book collections are recorded and well organized. For this reason, through community service activities, the authors intend to assist teachers in understanding the management of library administration. The activities carried out on August 16 - September 3, 2022. The target of this community service activity is teachers at MI Jampang who can become teachers as well as librarians who can manage library administration in the future. This community service method was in the form of involving several students in rearranging/sorting book collections. The forms of this activity were reordering/sorting books according to genre, classifying books using e-DDC, providing samples of book classification and socializing the use of e-DDC to teachers. This program had three objectives, namely to improve the quality of the library, provide education on how to manage library administration and to facilitate the search for users. The result of this service activity was  that teachers could understand how to manage library administration so that in the future, collections that increased and could only be managed properly. In conclusion, the existence of a library administration management work program at MI Jampang could help teachers to manage book collections in the library so that if it was  managed properly, students could  easily read books according to the genre they wanted  to read.